Analysis of Soft Soil Improvement Using Prefabricated Vertical Drains (PVD): A Case Study of Rorotan, Cilincing, North Jakarta - Hariati, Feril; Chayati, Nurul; Jannah, Lifa Raudhatul (Universitas Ibn Khaldun Bogor, 2025)
Soft soils in the Rorotan area of North Jakarta frequently encounter significant stability and settlement issues, which can affect the structures situated on them. This study focuses on applying the Prefabricated Vertical Drain (PVD) method to expedite the soil consolidation process, aiming to enhance soil strength and reduce the potential for settlement. The analysis uses boring log data and laboratory test results from the RDF construction project as secondary data and includes calculations of settlement magnitude and consolidation duration. The study results indicate that PVD installation considerably speeds up soil consolidation and improves soil bearing capacity compared to conventional soil improvement techniques. Using Prefabricated Vertical Drains (PVD) of 100 mm x 30 mm and a depth of 12 meters, the consolidation process can be shortened to just a few months. For PVD spacing of 1.5 meters, the consolidation time can be reduced to 6 months. With 1.8 meters spacing, it becomes 12 months; 2 meters spacing requires 15 months; 2.5 meters spacing takes 27 months; and 3 meters spacing needs 39 months. The study highlights a reduction in consolidation time from 277.58 months with a settlement of 0.835 meters to a few months, depending on the spacing used, reflecting a 97.8% reduction in time.